Stratigraphy, pollen history and geochronology of tidal marshes in a Gulf of Maine estuarine system: Climatic and relative sea level impacts - Ward, Larry G.; Zaprowski, Brent J.; Trainer, Kevin D.; Davis, P. Thompson (MARINE GEOLOGY, 2008)
Sedimentologic and stratigraphic characteristics of five tidal marshes in Great Bay Estuary, New Hampshire, which is located on the western boundary of the Gulf of Maine, were assessed from 20 vibracores. detailed descriptions of surficial environments, pollen analyses, and radiocarbon dating. Modern marsh sequences in Great Bay Estuary initiated with a time-transgressive basal peat that formed at the upland-brackish marsh boundary. The oldest basal peat deposit sampled during this study was dated at similar to 4560 cal yr B.P (based on an age of 4060 +/- 40 C-14 yr B.P.). The original tidal marshes that formed in Great Bay Estuary apparently were unable to accrete at a high enough rate to allow seaward expansion, resulting in a transgressive sequence of low marsh or mudflat sediments overlying the basal peat. The transgressive tidal marsh sequence is capped by high marsh sediments that corresponded to a slowing of relative sea-level (RSL) rise in the region and regressive seaward expansion of the tidal marshes. However, significant variations from these transgressive-regressive sequences occur in the Great Bay tidal marshes as a result of more recent marsh expansion and tidal channel migrations. Detailed pollen analyses of a vibracore taken in a tidal marsh along Squamscott River with a sedimentary record spanning the last similar to 3900 cal yr B.P exhibit five well-documented marker horizons including: 1) an increase of Tsuga (hemlock); 2) the appearance of Picea (spruce); 3) Tsuga and Fagus (beech) declines; 4) an increase in Ambrosia (ragweed) coupled with a sudden decrease in Quercus (oak); and 5) the Castanea (chestnut) decline. Using published ages for these pollen horizons and a calibrated 14C age obtained during this study for a basal peat, accretion rates for this marsh system over five time intervals were calculated: 1) 0.4 to 0.5 mm yr(-1) from similar to 3900 to 2850 cal yr B.P.; 2) 0.6 mm yr(-1) from similar to 2850 to similar to 1960 cal yr B.P.; 3) 0.8 mm yr(-1) from similar to 1960 to similar to 580 cal yr B.P.; 4) 0.7 to 0.8 mm yr(-1) from similar to 580 to similar to 210 cal yr B.P.: and 5) 0.8 to 0.9 mm yr(-1) over the last 210 years. The long-term accretion rate for the entire sequence based on the calibrated C-14 age of the basal peat was 0.6 to 0.7 mm yr(-1). This result agrees with accretion rates determined from calibrated C-14 ages from two other tidal marsh systems in Great Bay Estuary with accretion rates between similar to 0.6 to similar to 0.8 mm yr(-1). Higher accretion rates were obtained at a nearby tidal marsh with 1.2 mm yr(-1) for just the marsh and 1.3 mm yr(-1) for the marsh and underlying subtidal sediment. The results of this study indicate that the sedimentology and stratigraphy of moderate-size tidal marshes in rocky, glaciated coasts are highly variable and are strongly influenced by complex interactions among RSL, climatic variations, and anthropogenic influences. For instance, the early development of many of the marshes in the Great Bay Estuary area were likely driven by changes in rates of RSL resulting in transgressive onlap boundaries, subsequently overlain by regressive intertidal marsh sequences. However, more recent changes in tidal marsh sediment composition deposited during a relatively slow, steady RSL rise likely result from other forcings. such as changes in minerogenic and orogenic sediment inputs due to anthropogenic effects, tidal channel migrations, major storms causing erosion of the marsh, or climatic changes causing shifts in sediment delivery or vegetation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: accretion; climate effects; pollen; relative sea level; salt marshes; sedimentology; stratigraphy